Disposal of the Dead in Recently Abandoned Settlement Areas — an Evidence of the Siege of Olbia Pontica by Zopyrion? - Fornasier, J.; Ivchenko, A.V.; Kuzmishchev, O.H. (Археологія, 2024)
The present contribution focuses on extraordinary features with human remains of the 4th century BC which have been discovered to the west of the core city area of Olbia Pontica. There are numerous multiple burials within former settlement structures. The deceased were put in them without any grave goods, mainly in irregular positions and in some cases with obvious traces of external violence. Based on the archaeological finding, which is presented here for the first time exhaustively, we review the suggestion of previous research: a possible connection of these features with human remains with the siege of the city by the Macedonian general Zopyrion, which has been recorded in literature.